Feeding tomorrow: promoting Islamic dietary laws as a source of good health and well-being - Jaiyeoba, Haruna Babatunde; Amid, Azura; Jamaludin, Mohd Aizat (IIUM Press, International Islamic University Malaysia, 2020)
With the aim of promoting Islamic dietary laws as source of good health and well-being, International Institute for Halal Research and Training (INHART, IIUM) has been conducting several community engagement programs under the institute’s outstanding program called “Feeding Tomorrow” for secondary school students to ensure that safe, nutritious, and sustainable halal products are consumed and used by everyone in the community. Under this program, we have been able to gather brightest minds and expose them to theoretical and practical aspects of halal and halal industry, especially on meat and poultry, through halal slaughtering, and why it is essentially important to consume or use halal certified products. To a greater extent, the program has demonstrated an effective way for people to achieve good health resulted to protection of life and reason. Undoubtedly, Sharī‘ah seeks to achieve welfare, benefits, etc. and ward off evil, injury, loss, etc. for the creatures; and for these reasons, it has been made known that protection of life and ‘aql, among others, are integral parts of Maqāṣid al-Sharī‘ah. Similarly, ensuring healthy lives and promoting well-being for all at all ages is one of the Malaysian and United Nations’ (UN) 2030 agenda for sustainable development goals. In line with national and international agenda on good health and well-being, those participated in this program were also exposed to how to carry out basic animal slaughtering in halal way, identify halal certified products, understand the difference between lawful and unlawful, etc. At the end of this program in each school, questionnaires were distributed to determine students’ knowledge on Islamic dietary laws and 174 duly completed questionnaires were analyzed for this study. Having participated in this program, it was discovered that students are now knowledgeable about halal food, halal slaughtering, and halal logo. Hence, this program has been instrumental in realizing the essence of Maqāṣid al-Sharī‘ah and promoting SDG’s good health and well-being.